Nematus: a Toolkit for Neural Machine Translation - Sennrich, Rico; Firat, Orhan; Cho, Kyunghyun; Birch, Alexandra; Haddow, Barry; Hitschler, Julian; Junczys-Dowmunt, Marcin; Laubli, Samuel; Barone, Antonio Valerio Miceli; Mokry, Jozef; Nadejde, Maria (2017)
We present Nematus, a toolkit for Neural Machine Translation. The toolkit prioritizes high translation accuracy, usability, and extensibility. Nematus has been used to build top-performing submissions to shared translation tasks at WMT and IWSLT, and has been used to train systems for production environments.
arXiv:1703.04357